2012
DOI: 10.1007/s11420-011-9259-3
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Elution Characteristics of Vancomycin in a Composite Calcium Phosphate/Calcium Sulfate Bone Substitute

Abstract: Background: Periprosthetic joint infection is a particularly difficult orthopedic problem, complicating a growing number of revision procedures. Joint debridement and systemic antibiotics are the mainstay of treatment, yet difficulty remains in maintaining a minimum inhibitory concentration of antibiotic at the localized site of infection. Study Aims: This study analyzes the elution characteristics of a 40%bwt calcium phosphate-60%bwt calcium sulfate composite, at varying concentrations of vancomycin. Methods:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 29 publications
0
13
0
Order By: Relevance
“…On the contrary, a high content of gentamycin in the calcium sulfate resulted in a high antibiotic release through the high concentration gradient. Similarly, Yang et al reported that the calcium phosphate/calcium sulfate bone substitute with a higher vancomycin content also had a higher elution rate than that of a lower vancomycin content sample . In spite of a dose‐dependent elution rate of gentamycin‐loaded calcium sulfate samples was noticed, all samples showed antibacterial activity and inhibited the growths of S. mutans efficiently even under low‐dose.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…On the contrary, a high content of gentamycin in the calcium sulfate resulted in a high antibiotic release through the high concentration gradient. Similarly, Yang et al reported that the calcium phosphate/calcium sulfate bone substitute with a higher vancomycin content also had a higher elution rate than that of a lower vancomycin content sample . In spite of a dose‐dependent elution rate of gentamycin‐loaded calcium sulfate samples was noticed, all samples showed antibacterial activity and inhibited the growths of S. mutans efficiently even under low‐dose.…”
Section: Discussionmentioning
confidence: 96%
“…Previously, the influences of different antibiotics on the calcium sulfate were studied, and it was found that vancomycin, cefazolin, tobramycin, and amphotericin B extended setting time . Other studies reported that vancomycin did not influence the injectability and operability but changed the hydration progress and affected the in vivo absorption of calcium sulfate . However, the underlying mechanism for the influence of antibiotics on calcium sulfate remains unclear.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The authors assumed that surfactant-induced modification of crystalline morphology and size distribution may have contributed to the increase in setting time. Moreover, it was found that the in vivo absorption of calcium sulfate was prolonged when vancomycin was added [22]. Although the addition of vancomycin did not influence the operability or injectability from a syringe, the antibiotic obviously influenced the hydration of calcium sulfate.…”
Section: Discussionmentioning
confidence: 99%
“…When a high amount of vancomycin was added to the calcium sulfate, the high concentration gradient caused a high antibiotic release. Yang et al demonstrated the elution characteristics of vancomycin in a composite calcium phosphate/calcium sulfate bone substitute, and also concluded that the elution rates of the higher concentration groups were significantly higher than those of the lower concentration groups [22]. Although the antibiotic-loaded calcium sulfate samples showed dose-dependent elution rates of vancomycin, no difference was observed in the zones of inhibition among groups which indicates that vancomycin inhibits the growths of S. aureus efficiently even under low-dose.…”
Section: Discussionmentioning
confidence: 99%